THE ANALYSIS OF POTENTIAL SCENARIOS FOR THE SUSTAINABILITY OF GRAPE AGROTOURISM IN SANGGALANGIT VILLAGE, BULELENG REGENCY - Made Chandra Sintia Dewi Wulandari; Ida Ayu Nyoman Saskara (Adisam Publisher, 2025)
This study aims to analyze potential scenarios for the sustainable development of grape-based agrotourism in Sanggalangit Village, Buleleng Regency, and to identify the most effective scenario model to support the sector's long-term sustainability. The research is motivated by the current dominance of a production system focused on wine-making, limited product diversification, low participation of young farmers, and suboptimal stakeholder collaboration particularly with the private sector. A descriptive quantitative approach was employed, utilizing the SMIC-Prob Expert method as a probabilistic scenario analysis tool. Data were collected through questionnaires, in-depth interviews, field observations, and Focus Group Discussions (FGDs) involving 30 informants, including farmers, tourism managers, village and regency government representatives, and private sector actors such as Hatten Wines. Three main scenarios were analyzed: (1) maintaining the status quo of production, (2) market-driven product diversification, and (3) increasing local farmer participation, especially among the younger generation. The analysis reveals that the most favorable scenario is a combination of all three, with a stronger emphasis on product diversification and farmer participation. This integrated strategy is considered the most adaptive in responding to uncertainties while addressing structural challenges and leveraging development opportunities in grape-based agrotourism. Theoretically, the study reinforces the application of scenario analysis in local-based sustainable development planning. Practically, the findings offer guidance for policymakers and agrotourism stakeholders in designing training programs, facilitating innovation, and strengthening cross-sector collaboration to foster an inclusive and sustainable agrotourism ecosystem.